2021
DOI: 10.1039/d1ma00836f
|View full text |Cite
|
Sign up to set email alerts
|

Cation vacancy driven efficient CoFe-LDH-based electrocatalysts for water splitting and Zn–air batteries

Abstract: Rational design of multifunctional electrocatalysts can optimize the mutual conversion of water and oxygen. CoFe-LDH-based electrocatalyst with highly tunable electronic, component, and catalytic properties have attracted considerable attention. Herein, we...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 43 publications
0
5
0
Order By: Relevance
“…Ni3S4 [37], Co3O4/NF [38], B-Co3O4/NF [39], Mo-NiCo2O4/Co5.47N/NF [40], CoFe LDH [41], Co0.7Fe0.3P3 [42], NiS/NF [43], Fe-Co-S/Cu2O/Cu [44], Co0.89Fe0.11O-N [45],…”
Section: Electrocatalytic Oer Performancementioning
confidence: 99%
“…Ni3S4 [37], Co3O4/NF [38], B-Co3O4/NF [39], Mo-NiCo2O4/Co5.47N/NF [40], CoFe LDH [41], Co0.7Fe0.3P3 [42], NiS/NF [43], Fe-Co-S/Cu2O/Cu [44], Co0.89Fe0.11O-N [45],…”
Section: Electrocatalytic Oer Performancementioning
confidence: 99%
“…The host layer consists of mainly the active sites which are made of edge-sharing octahedral MO 6 units . Among the transition metals, particularly, Co-, Fe-, and Ni-based LDH materials are the most assuring metals for water electrolysis, although they have a less conductive nature due to their semiconducting or insulating nature, which affects the electron transfer process. Again, in particular, recent research demonstrated that a CoFe-based LDH in alkaline electrolytes exhibits enhanced OER performance due to its strong synergistic effect between Fe and Co ions, creating a favorable electronic structure and local coordination atmosphere. Here also, the working of the CoFe-LDH is still limited by its sluggish water dissociation process and low electrically conductive nature. , However, for practical application, an increase in the catalytic efficiency of this electrocatalyst was very much needed.…”
Section: Introductionmentioning
confidence: 99%
“…30,31 Also, the metal vacancies may provide adhesion sites for externally induced metal ions (in the case of intercalation) and therefore may enhance the intrinsic properties by synergic effect. 32,33 • Currently, metal-sulfide-based catalysts encounter many challenges such as surface oxidation, change in metal valence state, material dissolution, and phase transition in highly basic electrolytes under oxidation potential. Surface oxidation is one of the major issues while using alkaline electrolytes like KOH (pH = 14) where sulfides react with oxygen to form S�O bonds, leaving a metallic bond.…”
Section: Introductionmentioning
confidence: 99%
“…However, bulk CuSCN has poor charge-transport properties, which can be overcome by elemental doping, structural defects, and suitable interface engineering. , The intrinsic acceptor property of CuSCN is associated with a copper deficiency. Thus, the formation of copper deficiency (vacancy) might induce charge-transfer properties by acting as an active site and promoting contact with the intermediate species of HER. , Also, the metal vacancies may provide adhesion sites for externally induced metal ions (in the case of intercalation) and therefore may enhance the intrinsic properties by synergic effect. , ·…”
Section: Introductionmentioning
confidence: 99%